2001
DOI: 10.1046/j.1463-1326.2001.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of short and long duration insulinotropic agents on meal‐related glucose excursions

Abstract: These data support the impact of early and rapid insulin release in the control of prandial and post-meal glycaemia and demonstrate that a short anticipatory burst of insulin, restricted to the beginning of a meal, provides a clear metabolic advantage and prevents post-meal hypoglycaemic episodes when compared to a greater but reactive insulin exposure that follows a meal-induced increase in glucose excursion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…However, when the pharmacodynamics of these two agents have been compared directly in the perfused rat pancreas [10] or in vivo in rodents [11] it was found that the effects of nateglinide are more rapidly manifest and shorter in duration than are the effects of repaglinide. As reviewed recently [12], marked differences in the kinetics of ligand/receptor interactions and closure of the K + ATP channel seem to, at least in part, underlie the kinetic differences observed in vivo.…”
mentioning
confidence: 99%
“…However, when the pharmacodynamics of these two agents have been compared directly in the perfused rat pancreas [10] or in vivo in rodents [11] it was found that the effects of nateglinide are more rapidly manifest and shorter in duration than are the effects of repaglinide. As reviewed recently [12], marked differences in the kinetics of ligand/receptor interactions and closure of the K + ATP channel seem to, at least in part, underlie the kinetic differences observed in vivo.…”
mentioning
confidence: 99%
“…Glyburide failed to influence early insulin release and mealtime glucose excursions, but augmented postmealtime insulin concentrations and caused delayed hypoglycaemia. Although, glipizide and repaglinide both increased early as well as total insulin exposure and prevented mealtime glucose excursions [33] they caused delayed hypoglycaemia. These findings not only attest to the importance of early insulin release to mealtime glucose control but also suggest that nateglinide will have an improved safety and tolerability profile and greater potential to exert better mealtime glucose control, than either short-acting or long-acting SUs or repaglinide.…”
Section: Insulin Secretion In Vitromentioning
confidence: 95%
“…In the fasted state the insulin-stimulating effect of nateglinide is remarkably rapid in onset and short in duration [33]. This rapid on-off pharmacodynamic profile allows nateglinide to reduce or eliminate glucose excursions (during glucose tolerance tests or meals) without sustained or delayed hyperinsulinaemia and/or hypoglycaemia.…”
Section: Insulin Secretion In Vitromentioning
confidence: 99%
See 2 more Smart Citations